خواتین کی تعلیم اور سماجی تشکیل: مسلم مفکرین کی آراء، جدید فکری رجحانات اور تنقیدی جائزہ: Women’s Education and Social Formation: Muslim Thinkers’ Perspectives, Modern Intellectual Trends, and a Critical Review - Dr. Sobia Nosheen (Al-Amīr Research Journal for Islamic Studies, 2025)
Women’s education is not confined to individual development; rather, it plays a fundamental role in the moral, intellectual, and social construction of family and society. This paper presents a research-based and critical analysis of the historical evolution of women’s education, the causes of its decline, and the emerging intellectual trends in the modern era. The perspectives of prominent Muslim thinkers, particularly Sir Syed Ahmad Khan and Allama Muhammad Iqbal, are examined in the contemporary context. The study critically evaluates whether twentieth-century scholarly approaches remained aligned with authentic Islamic teachings. Furthermore, modern feminism is discussed as a reactionary movement, with an analytical assessment of its constructive and problematic dimensions. The study concludes that a balanced educational framework rooted in ethical values and Islamic principles is essential for sustainable social development. Keywords: Women’s Education, Social Formation, Muslim Thinkers, Intellectual Development, Feminism, Islamic Teachings